Non‐3d Metal Modulation of a 2D Ni–Co Heterostructure Array as Multifunctional Electrocatalyst for Portable Overall Water Splitting. Issue 10 (29th January 2020) - Liu, Wenxian; Yu, Linhai; Yin, Ruilian; Xu, Xilian; Feng, Jinxiu; Jiang, Xuan; Zheng, Dong; Gao, Xinlong; Gao, Xiaobin; Que, Wenbin; Ruan, Pengchao; Wu, Fangfang; et al.
Abstract: Portable water splitting devices driven by rechargeable metal–air batteries or solar cells are promising, however, their scalable usages are still hindered by lack of suitable multifunctional electrocatalysts. Here, a highly efficient multifunctional electrocatalyst is demonstrated, i.e., 2D nanosheet array of Mo‐doped NiCo2 O4 /Co5.47 N heterostructure deposited on nickel foam (Mo‐NiCo2 O4 /Co5.47 N/NF). The successful doping of non‐3d high‐valence metal into a heterostructured nanosheet array, which is directly grown on a conductive substrate endows the resultant catalyst with balanced electronic structure, highly exposed active sites, and binder‐free electrode architecture. As a result, the Mo‐NiCo2 O4 /Co5.47 N/NF exhibits remarkable catalytic activity toward the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), affording high current densities of 50 mA cm −2 at low overpotentials of 310 mV for OER, and 170 mV for HER, respectively. Moreover, a low voltage of 1.56 V is achieved for the Mo‐NiCo2 O4 /Co5.47 N/NF‐based water splitting cell to reach 10 mA cm −2 . More importantly, a portable overall water splitting device is demonstrated through the integration of a water‐splitting cell and two Zn–air batteries (open‐circuit voltage of 1.43 V), which are all fabricated based on Mo‐NiCo2 O4 /Co5.47 N/NF, demonstrating a low‐cost way to generate fuel energy. This work offers an effective strategy to develop high‐performance metal‐doped heterostructured electrode. Abstract : Non‐3d metal modulation of a 2D Ni–Co heterostructure array is demonstrated to effectively regulate the electronic structure of catalyst. The resultant material, i.e., Mo‐doped NiCo2 O4 /Co5.47 N heterostructure nanosheet array coated nickel foam (Mo‐NiCo2 O4 /Co5.47 N/NF), shows multifunctional electrocatalysis for the oxygen evolution reaction and hydrogen evolution reaction, which is then used for the construction of a Zn–air battery‐driven water splitting device.